Mechanisms linking active rock glaciers and impounded surface water formation in high‐mountain areas. Issue 2 (13th October 2017) - Colombo, Nicola; Sambuelli, Luigi; Comina, Cesare; Colombero, Chiara; Giardino, Marco; Gruber, Stephan; Viviano, Gaetano; Vittori Antisari, Livia; Salerno, Franco
Abstract: Rock glaciers are slowly flowing mixtures of debris and ice occurring in mountains. They can represent a reservoir of water, and melting ice inside them can affect surface water hydrochemistry. Investigating the interactions between rock glaciers and water bodies is therefore necessary to better understand these mechanisms. With this goal, we elucidate the hydrology and structural setting of a rock glacier–marginal pond system, providing new insights into the mechanisms linking active rock glaciers and impounded surface waters. This was achieved through the integration of waterborne geophysical techniques (ground penetrating radar, electrical resistivity tomography and self‐potentials) and heat tracing. Results of these surveys showed that rock glacier advance has progressively filled the valley depression where the pond is located, creating a dam that could have modified the level of impounded water. A sub‐surface hydrological window connecting the rock glacier to the pond was also detected, where an inflow of cold and mineralised underground waters from the rock glacier was observed. Here, greater water contribution from the rock glacier occurred following intense precipitation events during the ice‐free season, with concomitant increasing electrical conductivity values. The outflowing dynamic of the pond is dominated by a sub‐surface seepage where a minor fault zone in bedrock was found, characterised by altered and highly‐fractured rocks. The applied approach is evaluated here as a suitable technique for investigating logistically‐complex hydrological settings which could be possibly transferred to wider scales of investigation. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Rock glacier hydrology and structural setting of a marginal pond are investigated integrating waterborne geophysics and heat tracers. Rock glacier movement has modified the pond structure and water level. A sub‐surface hydrological window connects the rock glacier to the pond. Greater water contribution from the landform occurs following intense precipitation, with increasing electrical conductivity values. A sub‐surface seepage drives the outflowing dynamic of the pond. The applied approach could be transferred to wider scales of investigation.